Evaluating the Efficiency of Floating Hydroponic System and Nutrient Film Technique for Kailan (Brassica oleracea L.) Cultivation - Harsela, Chiska Nova (CV. Green Publisher Indonesia, 2025)
This systematic literature review evaluates the efficiency of two prominent soilless cultivation systems—Floating Hydroponic System (FHS) and Nutrient Film Technique (NFT)—for kailan (Brassica oleracea L.) production. A search of 97 studies published between 2021 and 2025 was conducted to compare the performance of these systems. Both FHS and NFT demonstrated superior performance over conventional soil cultivation, with distinct advantages based on operational context. FHS showed better water use efficiency (35-45% reduction), simplified management, and lower investment costs, making it ideal for small to medium-scale operations. Conversely, NFT offered faster growth rates (15-25% increase), higher yield potential (20-30% increase), and superior oxygen delivery to roots (DO levels 7-9 mg/L), though it required more advanced monitoring systems. Both systems showed comparable quality in terms of leaf chlorophyll content, glucosinolate levels, and antioxidant capacity when properly managed. The review identified optimal NPK ratios, EC levels (1.5-2.5 dS/m), and pH ranges (5.5-6.5) for kailan. Economic analysis revealed lower operational costs for FHS (15-20% reduction), while NFT was more efficient in space utilization (40-50% higher plant density). This review offers evidence-based recommendations for system selection, advancing sustainable urban agriculture and food security initiatives.